MULHERES, ESPAÇO RURAL E O PINTOR HAIMON. ANÁLISE DO LÉCITO ÁTICO DO MUSEU NACIONAL DO RIO DE JANEIRO - Chevitarese, André Leonardo (PHOÎNIX, 2020)
This paper purports to publish and analyze the Athenian blackfigure lekythos (National Museum -Federal University of Rio de Janeiro) of the Haimon Painter.